Concept Analysis of Adaptive Learning Strategy in English Language Teaching (ALS-ELT) - Mark N., Saldivar, John; Bernadeth L., Fernandez (International Journal of Social Sciences and English Literature, 2024)
Adaptive Learning Strategies (ALS) are revolutionary forces in the ever-changing educational landscape, where varied learning contexts and technological breakthroughs converge. This study aimed to acquire a nuanced understanding of the concept while providing empirical support and new information on the usefulness and effects of ALS on language learning outcomes. Research articles from open-access databases such as Google Scholar, CrossRef, and OpenAlex published from 2019-2024 were carefully analyzed using Walker and Avant’s eight-step analysis. Keywords utilized were adaptive learning, knowledge translation, and English language teaching. The 17 research articles analyzed determined five attributes of adaptive learning pedagogy: enhanced motivation and involvement, personalization and customization, improvement in language proficiency and communication skills, support for autonomous and independent learning, and technological integration and innovation. Antecedents included five themes: learner needs and context, availability of technology and resources, teacher training and proficiency, administrability support and policy alignment, and student motivation and engagement. Consequences also generated five themes: personalized learning experiences, enhanced technological integration and innovative learning tools, effective implementation of ALS, institutional commitment to ALS adoption, active student participation, and improved learning outcomes. Adaptive learning strategy in English language teaching (ELT) effectively engages students by aligning content with their interests and providing relevant challenges, fostering active participation and motivation. Individualized learning paths and real-time feedback enhance learning outcomes, improving language proficiency and communication skills. The seamless incorporation of technology, such as language learning apps and AI-driven tools, enables personalized experiences and data-driven adaptation, promoting student autonomy and independence.